2021
DOI: 10.3389/fped.2021.675606
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Lactoferrin in the Prevention of Antibiotic-Associated Diarrhea in Children: A Randomized Clinical Trial

Abstract: Introduction: Antibiotic-associated diarrhea (AAD) is a common adverse reaction to antibiotic treatment affecting up to 21% of children. The aim of the study is to evaluate whether bovine lactoferrin (bLf) might be used for AAD prevention.Materials and Methods: In this prospective, randomized, double-blind, placebo-controlled, single-center study, we enrolled 156 children aged between 1 and 18 years, treated with antibiotic due to acute respiratory or urinary tract infection. We randomly allocated children 1:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several studies assessed the efficacy of lactoferrin in neonates, infants, and children on gut health and neonatal sepsis and found that it is effective with almost no adverse effects. 10 , 11 The efficacy of lactoferrin in the treatment of IBD-related anemia was not previously studied. Therefore, the aim of this study was to compare the effect of lactoferrin versus oral ferrous sulfate as an iron supplement in the treatment of IDA in children with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies assessed the efficacy of lactoferrin in neonates, infants, and children on gut health and neonatal sepsis and found that it is effective with almost no adverse effects. 10 , 11 The efficacy of lactoferrin in the treatment of IBD-related anemia was not previously studied. Therefore, the aim of this study was to compare the effect of lactoferrin versus oral ferrous sulfate as an iron supplement in the treatment of IDA in children with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteroidetes and Firmicutes account for 90% of the human GM (Jandhyala SM et al 2015). The proportions of Firmicutes, including Listeria and Streptococcus, are reported to decrease in response to diseases (Lanza VF et al 2015;Wronowski MF et al 2021). Gram-positive bacteria, such as Lactococcus, Lactobacillus, and Listeria, help to maintain the composition of the GM and prevent pathogen invasion (Garneau JE et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are similar to those of Li ( 43 ) on the effect of Astragalus membranaceus polysaccharides on intestinal flora diversity of AAD diarrhea mice. Firmicutes are usually the representative of the intestinal flora of healthy individuals and may decrease with the occurrence of diseases ( 44 ). They contain a large number of Gram-positive bacteria, such as Lactococcus, Lactobacillus, Listeri , and so on, most of which are considered beneficial bacteria, helping to maintain the intestinal flora balance and prevent pathogen invasion ( 45 ); However, Bacteroidota is composed of common intestinal disease-related microorganisms, which have a relatively high risk of diarrhea and other diseases and are negatively correlated with inflammatory cytokines ( 46 ).…”
Section: Discussionmentioning
confidence: 99%